Prevalence of Diabetes Mellitus Comorbidity in Hypertension Patients: Indonesian National Health Insurance Data - Resa Paksi Mandariska; Adzka Fahma Rodliya; Siti Hanisa Khaira (OVUM : Journal of Midwifery and Health Sciences, 2026)
Managing hypertension becomes significantly more complex when diabetes mellitus co-occurs, often leading to poorer clinical outcomes and higher healthcare costs. This research investigated the prevalence of diabetes comorbidity among hypertensive patients at advanced referral health facilities and its relationship with patient age. Using a cross-sectional approach, we analyzed 5,505 records from the 2025 Indonesian National Health Insurance (BPJS Kesehatan) sample data for patients presenting with a primary diagnosis of hypertension. The overall prevalence of comorbid diabetes was 9.3% (510 cases). Within this cohort, 57.6% (3,172) were non-elderly (<60 years) and 42.4% (2,333) were elderly (?60 years). Diabetes prevalence was 9.6% in the elderly group and 9.0% in the younger demographic. The Pearson Chi-Square analysis confirmed no significant association between age category and diabetes (p = 0.459). These findings suggest that the risk of comorbid diabetes among referred hypertensive patients remains consistent regardless of age. Therefore, we recommend universal endocrine screening for all hypertensive referrals to prevent delayed diagnosis and improve targeted interventions, rather than relying on age-based screening protocols.